2020
DOI: 10.1002/lary.28538
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety and Quality Improvement in Otolaryngology–Head and Neck Surgery: A Systematic Review

Abstract: Objective The current landscape of patient safety/quality improvement (PS/QI) research dedicated to Otolaryngology–Head and Neck Surgery (OHNS) has not been established. This systematic review aims to define the breadth and depth of PS/QI research dedicated to OHNS and to identify knowledge gaps as well as potential areas of future study. Methods The study protocol was developed a priori using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) process. A computerized Ovid/Medline d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A recent systematic review of the otolaryngology-HNS literature identified equitable care as the least studied quality domain, with only 6 of the 738 (0.8%) PS/ QI studies addressing it. 16 Greater diversity is required in Regent to ensure equitable care in an evidence-based fashion, to identify relevant social determinants of health, and to address otolaryngology-HNS disparities. The AAO-HNS/F is committed to diversity and overcoming associated barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of the otolaryngology-HNS literature identified equitable care as the least studied quality domain, with only 6 of the 738 (0.8%) PS/ QI studies addressing it. 16 Greater diversity is required in Regent to ensure equitable care in an evidence-based fashion, to identify relevant social determinants of health, and to address otolaryngology-HNS disparities. The AAO-HNS/F is committed to diversity and overcoming associated barriers.…”
Section: Discussionmentioning
confidence: 99%
“…It is equally important to note that equitable care is 1 of the 6 domains of quality health care per the Agency for Healthcare Research and Quality 15 . Equitable care is defined as “providing care that does not vary in quality because of personal characteristics such as gender, ethnicity, geographic location, and socioeconomic status.” A recent systematic review of the otolaryngology‐HNS literature identified equitable care as the least studied quality domain, with only 6 of the 738 (0.8%) PS/QI studies addressing it 16 . Greater diversity is required in Reg‐ent to ensure equitable care in an evidence‐based fashion, to identify relevant social determinants of health, and to address otolaryngology‐HNS disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The need to provide better care for patients led to the Institute of Medicine's recommendation for hospitals to develop a culture that fosters patient safety (Kohn & Donaldson, 2000). In addition to these recommendations, the implementation of safe practices depends on developing a positive patient safety culture (Gettelfinger et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…n recent years, there has been a national increase in awareness and discussion around disparities in pediatric otolaryngology care 1 as well as calls for further characterization of these disparities. 2,3 Large disparities in access to high-quality and affordable surgical care are present in the United States and globally. 3 There are many factors such as race, ethnicity, and socioeconomic status (SES) that contribute to disparities in pediatric otolaryngology care.…”
mentioning
confidence: 99%